2009
DOI: 10.1007/s00253-009-1927-6
|View full text |Cite
|
Sign up to set email alerts
|

rep-PCR fingerprinting and taxonomy based on the sequencing of the 16S rRNA gene of 54 elite commercial rhizobial strains

Abstract: In tropical soils, diversity and biotechnological potential of symbiotic diazotrophic bacteria are high. However, the phylogenetic relationships of prominent strains are still poorly understood. In addition, in countries such as Brazil, despite the broad use of rhizobial inoculants, molecular methods are rarely used in the analysis of strains or determination of inoculant performance. In this study, both rep-PCR (BOX) fingerprintings and the DNA sequences of the 16S rRNA gene were obtained for 54 rhizobial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 26 publications
4
38
0
4
Order By: Relevance
“…The average size of isolated 16S rDNAs of the 20 slow-growing STB strains around 1450 bp were in the same range previously reported 27,28 . However, sequences of only one gene, 16S rDNA, cannot be used to resolve differences amongst natural variants of the 7 B. elkanii and 6 B. japonicum STB strains observed in PCR-DNA fingerprints ( Fig.…”
Section: Discussionsupporting
confidence: 73%
“…The average size of isolated 16S rDNAs of the 20 slow-growing STB strains around 1450 bp were in the same range previously reported 27,28 . However, sequences of only one gene, 16S rDNA, cannot be used to resolve differences amongst natural variants of the 7 B. elkanii and 6 B. japonicum STB strains observed in PCR-DNA fingerprints ( Fig.…”
Section: Discussionsupporting
confidence: 73%
“…observed in our study. In contrast, other studies have found poor correlation between genotyping (rep-PCR) and DNA sequencing methods used to determine species/strain relationships of other bacterial genera (4,19). The 16S rRNA gene sequence of an environmental strain of Lactococcus garvieae served as an effective outgroup for the 16S rRNA gene dendrogram (Fig.…”
Section: Downloaded Frommentioning
confidence: 68%
“…There was no evidence of codiversification (ParaFit; P ϭ 0.5129). Five species of Largidae from geographically distant areas (Argentina, Colombia, Costa Rica, Mexico, and the United States) harbored the same or very similar strains of Burkholderia, which closely matched the 16S rRNA sequences of PBE clade Burkholderia, including those of curated elite commercial inoculants used in agriculture for nodulation of legume crops in Brazil, housed in the SEMIA Rhizobium Culture Collection (e.g., 100% identical to Burkholderia SEMIA 6385 [GenBank accession number FJ025136.1] and SEMIA 6382 [GenBank accession number AY904775.1], iso-lated from Piptadenia gonoacantha and Mimosa caesalpiniifolia roots, respectively [54]). …”
Section: Resultsmentioning
confidence: 99%